2008
DOI: 10.1177/1077801208315528
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Sexual Assault Across the Life Span Among Incarcerated Women

Abstract: This study investigated the prevalence of and associations among sexual assault by life stage (childhood, adolescence, or adulthood) and perpetrator (family, stranger, friend, or partner) via a survey of a statewide sample of incarcerated women (N = 484). Participants were 18 to 56 years old, and the majority were White (56%). Results demonstrate higher rates of sexual assault in childhood (35%) and adulthood (22%) as compared with adolescence (14%). Logistic regression analyses revealed significant associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 45 publications
(87 reference statements)
3
43
0
Order By: Relevance
“…Learning more about this vulnerable group is equally important for the prison system, which is responsible for providing a variety of health services to accommodate their special needs. With the majority of women who enter prison sharing similar socioeconomic backgrounds of poverty, abandonment, and negative childhood experiences (Messina & Grella, 2006;Talvi, 2007), learning more about the long-term consequences of sexual victimization on the health and well-being of incarcerated women is more important than ever (Maeve, 2000;McDaniels-Wilson & Belknap, 2008;Raj et al, 2008;Thomas, Joshi, Wittenberg, & McCloskey, 2008). Statistics.…”
Section: Trauma and Victimization Manifestationsmentioning
confidence: 95%
See 3 more Smart Citations
“…Learning more about this vulnerable group is equally important for the prison system, which is responsible for providing a variety of health services to accommodate their special needs. With the majority of women who enter prison sharing similar socioeconomic backgrounds of poverty, abandonment, and negative childhood experiences (Messina & Grella, 2006;Talvi, 2007), learning more about the long-term consequences of sexual victimization on the health and well-being of incarcerated women is more important than ever (Maeve, 2000;McDaniels-Wilson & Belknap, 2008;Raj et al, 2008;Thomas, Joshi, Wittenberg, & McCloskey, 2008). Statistics.…”
Section: Trauma and Victimization Manifestationsmentioning
confidence: 95%
“…When examining a statewide sample of incarcerated women (N ¼ 484), Raj et al (2008) found that one in three women were sexually abused before the age of 18, with the average age being 9.6 years. Although the authors reported that 47% of their sample was sexually abused between 12 and 17 years of age, 29% of all forcible rapes occurred when the victim was younger than 11 years of age.…”
Section: Prevalence Of Sexual Abusementioning
confidence: 99%
See 2 more Smart Citations
“…Given that women's motivations for violence and the victims of their violent behaviors frequently differ from those of male-perpetrated violence (Kruttschnitt, 2002;Mann, 1990Mann, , 1996Pollock & Davis, 2005) and that multiple studies have found gender differences when comparing incarcerated men and women (e.g., Fazel et al, 2006;James & Glaze, 2006;Kubiak et al, 2010;Messina, Burdon, Hagopian, & Prendergrast, 2006;Raj et al, 2008), gender-specific and trauma informed services are needed for incarcerated women (Bloom, Owen, & Covington, 2003;Fournier, Hughes, Hurford, & Sainio, 2011;Laux et al, 2008). In particular, incarcerated females with violent offenses represent a distinct population in need of interventions that consider differences in mental health, substance use, anger regulation, and exposure to interpersonal violence and their the women's connections to engagement in violence.…”
Section: Intervention Needs For Incarcerated Women With Violent Offensesmentioning
confidence: 99%